DAMPAK PENGGUNAAN YOUTUBE DALAM MENANAMKAN NILAI AGAMA DAN MORAL PADA ANAK USIA 5-6 TAHUN - Herniawati, Ani; Rahmawati, Risa; Hidayat, Yusuf; Tya, Sandi (Jurnal Intisabi, 2025)
The development of religious and moral values is the ability of early childhood to act and behave according to the religious and moral values he/she embraced. This study aims to find out the effect of using Youtube to instill religious and moral values for early childhood in Kober El Karim, and to find out the benefits of using Youtube for early childhood in Kober El Karim. The method used in this study is a qualitative under a phenomenological approach. The results of this study showed that the use of Youtube has an effect to instill religious and moral values for early childhood in Kober El Karim in the form: the early childhoods read basmalah in every activity, the early childhoods feel more enthusiastic to pray before and after studying, before and after eating snacks, and before going home. In addition, the early childhoods try to tell honestly and maintain noble characters while at school. In addition, the use of Youtube for early childhoods at Kober El Karim is useful in fostering their creativity according to what they watch, developing their motor aspect, and increasing their linguistic vocabulary. In conclusion, the use of Youtube has positive effect to instill religious and moral values for the early childhoods in Kober El Karim, Ciamis Regency.